Dealing with water scarcity: the importance of social capital in areas susceptible to desertification in the Brazilian semiarid region - FAUSTINO, JENNIFER CICERA DOS SANTOS; Lima, Patrícia Verônica Pinheiro Sales de; Casimiro Filho, Francisco; Rodrigues, Maria Ivoneide Vital (Sustainability in Debate, 2016)
The purpose of this article wisas to analyze how indicators of social capital are related with the perceptions of rural community leaders and with their ability to deal with water scarcity caused by periodic droughts in the semiarid region. For that purpose, we conducted an empirical study in rural communities living in "Areas Susceptible to Desertification" (ASDs) located in state of Paraíba, Brazil. Methods employed were descriptive statistics (using means and standard deviations), construction of an index of social capital and the Eta correlation coefficient. Results show that, according to their leaders, communities have a low level of social capital and weak capacity to deal with water scarcity, despite the existence of social technologies. The analysis of the relationship between these variables indicated the need for investments in social capital as a way to increase the performance of rural communities to confront water scarcity in Paraíba.